Promising methods for assessing the degree of thermal damage obtained under fire conditions made with the application of gypsum boards - Surikov Андрей Валерьевич; Zaynudinova Наталья Владимировна; Boyko Василий Павлович (Journal of Civil Protection, 2022)
Purpose. To determine promising methods for assessing the degree of thermal damage to structures made using gypsum boards (hereinafter referred to as drywalls) received under fire conditions. Methods. Analysis of the results of existing studies and methods for assessing the degree of thermal damage to structures made using drywalls under fire conditions. Laboratory studies of samples of gypsum boards in a muffle furnace under temperature exposure. Findings. Based on the results of a review of literature sources, promising methods for assessing the degree of thermal damage to structures made with the use of drywalls were identified under fire conditions. The well-known method of visual assessment of drywall damage in case of fire was adapted for the purpose of its application on the territory of the Republic of Belarus. It has been experimentally established that the visual method for assessing the degree of thermal damage to various types of drywalls has low information content at certain temperature ranges. Application field of research. The obtained research results can be used when examining a fire site to determine the source of the fire, propagation paths, conditions and dynamics of combustion development, as well as in the development of technical means for determining the degree of thermal damage to structures made from drywall sheets received under fire conditions.